Virtual Reality Simulations for Hospital Fire Evacuation: A Systematic Literature Review - Martin, Victor Biagiotti Saint; Palmeira, Eduardo Gabriel Queiroz; Gonçalves, Victor Barbosa; dos Santos, Leonardo Nery Carrijo; Melazzo, José Júlio Morais; Lamounier Júnior, Edgard Afonso; Cardoso, Alexandre (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
A Health Care Establishment (HCE) aims at treating, medicating, curing, and sheltering individuals with health needs. It is not expected that this type of establishment poses a threat to the life of any individual. However, like any other establishment, HCE is vulnerable to human failures that can represent an imminent danger to an individual's life. Between 2012 and 2014, approximately 1,100 annual cases of hospital fires were recorded in the USA. Thus, hospital staff training regarding the evacuation of hospitalized individuals emerges as an essential practice in reducing the number of deaths and injuries in the face of this kind of disaster. Given this scenario, new technologies have been used in evacuation training, such as Virtual Reality (VR). Therefore, this paper aims to summarize the state-of-the-art concerning the fire evacuation training in hospitals using VR through a systematic literature review. The applied search string returned 172 papers. After a rigorous selection process, 5 studies were included in the review. Most of the studies addressed some negative aspects concerning traditional evacuation training, thus encouraging the use of virtual environments for training, where it is possible to immerse the user in extreme simulated fire situations in hospitals. Also, a comparative analysis of the financial costs between traditional and VR training, between methods and technologies for VE training implementation, and some limitations of applying the VR technology were identified as the most relevant information. To conclude, it is encouraged new VR studies related to hospital fire evacuation training.